Supporting Export Competitiveness through Port and Rail Network Reforms : A Case Study of South Africa - Pieterse, Duncan (World Bank, Washington, DC, 2016)
Transport and logistics infrastructure is a critical determinant of the competitiveness of a country's producers and exporters. Well-functioning transport and logistics infrastructure relies not just on hardware, but critically on the operating environment that emerges from the interaction between private sector operators; national policies and regulatory regimes; and, in many countries, state-owned owners and operators of core infrastructure. This paper looks at the case of South Africa, where constraints in access, pricing, reliability, and network interfaces, particularly in the port and rail network, are eroding the competitiveness of South African exporters. The paper draws on interviews with a wide range of exporters along with secondary research to examine South Africa's port and rail network, and explores the underlying factors contributing to these constraints, including chronic underinvestment, an inadequate regulatory environment, insufficient private sector participation, and weak regional integration. The paper concludes with a review of the reforms needed to deliver a more broadly accessible and competitive rail and port sector based on international case examples. It highlights the need for institutional reforms to promote competitive pricing; private sector participation to increase investment and improve service delivery; information and coordination to address market failures and improve access; and cooperation to improve intermodal, interregional, and institutional interfaces.